AN ANALYSIS OF NON-VERBAL COMMUNICATION IN ACADEMIC PRESENTATION - Yudi Juniardi; Dina Rachmawati; Rendi Pata Serpa (Jurnal Bebasan, 2018)
The research aims to investigate the use of non-verbal communication in academic presentation and to describe the reasons of the use of non-verbal communication by students of the in academic presentation at English department, University of Sultan Ageng Tirtayasa. Qualitative method was employed in this research particularly case study design. The participants were three students of fourth semester of English department who were taking public speaking subject. To collect the data, three techniques were employed; observation, questionnaire, and interview. The researcher used observation to find out the types of non-verbal communication in academic presentation. The questionnaire and interview were used to answer the reasons toward the use of non-verbal communication in academic presentation. Afterwards, the data were further analyzed by using qualitative data analysis method of Miles, Huberman, & Saldana theory. The data analysis showed that: gesture was non-verbal communication which the most frequently used by the students. Moreover, students preferred to use gesture and eye contact: The former was used to help conveying the communicative more easily, the later was used to make the presentation more interesting. It can be stated that non-verbal communication is helpful for the students in making presentation performance.